Exploring Students’ Readiness in Blended Leraning in EFL Context - Gina Larasaty; Ginsa Oktaviani (National Conference on Language, Education, and Technology Proceeding, 2022)
Nowadays, technology is widely viewed as a platform in EFL teaching that integrates online and offline. Although much of the study investigates the Blended Learning method in EFL teaching, relatively little empirical evidence reports students' readiness for Blended Learning. To fill this gap, this study is aimed to know how students' readiness for Blended Learning is situated in the Senior High School context. Grounded in qualitative research with survey design, this survey is distributed to 108 students from SMAN l Indramayu in the academic year 2021 / 2022. This research showed that students have low readiness levels in the English language Blended Learning in which they scored 2.71 out of 4.00. These indicate that senior high school students are not ready to learn English using Blended Learning. This can be seen from the students' attitude. The student's attitude showed that 1). most students want to access the teaching materials and the English lessons without limits of time and place. 2). most students felt that they got bored when studying online. 3). most of them stated they missed assignment due dates in an online learning activity. 4). most students said they like the fast feedback when they meet their teacher in person. However, they have a positive opinion Web is a helpful platform for learning.